Mapping of FMCG brands using Brand Apostle Model and the Impact of Customer Satisfaction on its Repurchase in Sultanate of Oman - Kumar R., Renjith; Fernandez, Diana (British Journal of Marketing Studies, 2019)
This research aims to map few FMCG brands on brand apostle model and to analyse the impact of consumer’s satisfaction on future purchase. Five products are selected Shampoo, Milk, Toilet soap, Toothpaste and Juice for the study. A sample of 212 Omani households are contacted for collection of responses from Nizwa. All the brands are positioned in the loyalists category and few are categorized as brand apostles. Among the shampoo brands, Tresemme and Vatika are brand apostles. Among the toothpaste brands, Pepsodent and Oral B are brand apostles in the toothpaste category. Johnson and Johnson, Nivea and Pears are brand apostles among toilet soap brands. Suntop is the brand apostle in the juice category. The correlation between the satisfaction and future preference is analysed. The contribution and the impact of satisfaction of each brands on future purchase for each product is assessed.